American law yearbook 2015 - Tyrkus, Michael J.; Gale Group (Farmington Hills, Michigan Gale, Cengage Learning, 2016)
Annual supplement to the Gale Encyclopedia of American Law that updates and expands the content with new topics, updates, biographies of prominent figures and government appointees, and other features. Each year's edition contains the full U.S. Supreme Court docket in addition to the non-Supreme Court cases.
Abortion -- Abuse of power -- Affirmative action -- Agricultural law -- Americans with disabilities act -- Antitrust law -- Arbitration -- Bankruptcy -- Banks and banking -- Capital punishment -- Civil procedure -- Civil rights -- Collective bargaining -- Commerce clause -- Confrontation -- Copyright -- Criminal law -- Discrimination -- DNA evidence -- Drugs and narcotics -- Due process -- Education law -- Eighth amendment -- Election law -- Employment discrimination -- Environmental law -- ERISA -- Ex post facto laws -- Fair housing act -- Family law -- Federal Communications Commission -- Fifth amendment -- First amendment -- Flash-mob crime -- Fourth amendment -- Fraud -- Freedom of religion -- Freedom of speech -- Gambling -- Gay and lesbian rights -- Gun control -- Habeas corpus -- Health care -- Health law -- Immigration -- Immunity -- Implied consent -- Insider trading -- Jurisdiction -- Jury -- Juvenile law -- Labor law -- Legal education -- Military -- Murder -- National security -- Patents -- Police -- Preemption -- Prisoners' rights -- Product liability -- Racial discrimination -- Second amendment -- Securities -- Sentencing -- Separation of powers -- Sex offenses -- Sexual assault -- Sovereign immunity -- Sports law -- Supremacy clause -- Telecommunications -- Terrorism -- Tobacco -- Torture -- Trademarks -- Truth in lending act -- Veterans' rights -- Voting rights -- Water rights -- Whistleblowing.
"ISSN 1521-0901."
"A guide to the year's major legal cases and developments."
Includes bibliographical references and indexes.
Keywords: Law -- United States; Law -- United States -- Periodicals; Law -- United States -- Popular works; Justice, Administration of -- United States; Courts -- United States; Lawyers -- United States; Judges -- United States; Law -- Cases